Barriers to technology integration in Islamic education: An insight of excellent teachers - Saad, N. (2015)
This paper addresses the insight of excellent teachers of Ministry of Education, Malaysia towards barriers in integration of technology in Islamic Education in school. More specifically, this paper focused on how excellent teachers think about the barriers in technology integration and how teachers initiate's and utilize a technology framework for effectiveness. It is an excerpt from a big research of technology integration in Malaysia. The research design employed qualitative methods to examine the phenomena and identify issues and solutions from the empirical investigations. The case study concludes factors of integration and practical solutions by the practitioners. Furthermore, the article also delves into a framework of learning point for teachers to adopt and provides some helpful tips for technology use in the classroom and daily routines.